Tree Speech: An Analysis of Discourses on Permanent Reserved Forests in Malaysian Debates since 1959 - Azmi, Alia; Jenkins, Rhosanna (Forestry Faculty, Universitas Hasanuddin, 2021)
As a country that once relied heavily on the forestry industry, Malaysia is slowly trying to change their economic dependence to a more sustainable resource, however, the continued reliance on forest resources is creating a conflict between protection as well as development of the forest reserves. To better understand the conflict that exists within the debates among the political elites in Malaysia, this paper examines the speeches on permanent reserved forests by decision makers in the Malaysian Parliamentary debates. These parliamentary debates (n = 229) were analysed using content analysis where three major themes in PRFs were identified: (1) industry and economic development; (2) environmental protection, conservation and impact; and (3) social development and community rights. Results show that economic concerns related to agriculture, timber and development dominated the parliamentary debates throughout the early discussions and the topic of PRF has been framed as primarily an economic issue by the political elites throughout the period of analysis. While there have been environmental issues discussed frequently in the debates, little change has occurred in the discussions on PRFs, which means the fundamental policy underpinning the management of these forests has not changed since colonial times. Peaks in the discussion of permanent reserved forests are associated with key legislations and events within Malaysia. This analysis indicates that the governance of PRF is largely unchanged, and while the new government indicated change could occur, the fact that they fell within two years of election does not lend to a positive note. The analysis has implications for future governance of forestry in Malaysia, which is decidedly embedded within the principle of resource use, inherited from the British era. If forests are to be protected, the fundamental principle of resource use has to be reconstructed entirely.